Islamic Moderatism as a Form of Rejection to the Phenomenon of Phobia Due to Actions and Actions Radicalism and Terrorism in Indonesia - Rahman (International Journal of Educational and Life Sciences, 2024)
This article wants to explain Islamic moderation as part of our efforts to reject acts of radicalism and terrorism in Indonesia.The moderation taught by Islam is an explanation contained in the Koran which is known aswasathiyahwhich aims to produce people who have moderate qualities in every line of life. These qualities include tawasuth, tawazun, and tasamuh. The discussion in this article uses descriptive qualitative methods with the aim of providing an overview of a particular society or group of people or a description of a symptom or the relationship between two or more symptoms. The communities or groups in this research are those who have ideologies that conflict with Islam. The results of this research state thatRadicalism and terrorism can give rise to attitudes of hatred and discrimination against Islam and Muslims which are often called phobias. Therefore, to realize a friendly and gracious Islam, every Muslim individual should apply moderate principles in national and state life.